PENGEMBANGAN MEDIA PEMBELAJARAN E-MAS (E-MODUL IPAS) BERBASIS FLIPBOOK UNTUK MENINGKATKAN HASIL BELAJAR IPAS MATERI AKTIVITAS EKONOMI MASYARAKAT DI SDN WATES 02 NGALIYAN SEMARANG - Taufik, Ahmad; Prasetyaningtyas , Fitria Dwi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
Implementing innovative learning is a crucial component in achieving successful learning outcomes. Learning media and models in the current era strive to keep pace with the times and continuously follow technological advancements. The lack of innovative learning media that aligns with scientific and technological progress negatively impacts students, particularly in terms of material comprehension. Transforming print media into digital format through the use of flipbook-based E-modules presents a solution to this issue. This research aimed to develop E-MAS, an E-module for IPAS (Social Science), as a learning medium for grade V students at SDN Wates 02. The RnD (research and development) study employed the ADDIE model, comprising five stages. It involved all 28 students from grade V at SDN Wates 02 Ngaliyan Semarang. Data was collected through test and non-test methods and analyzed quantitatively. To assess the effectiveness of the E-MAS learning media, t-test and n-gain analyses were conducted. The material expert validation test achieved an average score of 91,66% with the "very feasible" criteria, while the media expert validation test also obtained an average score of 98,33% with the "very feasible" criteria. The t-test result was 0.000, and the n-gain result was 75.1382. These findings indicate that the E-MAS learning tool is highly suitable for educational activities and effectively enhances student learning outcomes, specifically in the IPAS subject of community economic activity material for grade V elementary school students.